Comparing Kahoot, Quizizz, And Wordwall In EFL Reading Class - Ibad, Wasilatul; Sabat, Yuliyanto; Musyarofah, Lailatul; Sulistyaningsih , Sulistyaningsih (Eduvest - Journal of Universal Studies, 2023)
The purpose of this study was to compare Kahoot, Quizizz, and Wordwall on student learning outcomes in reading classes. The urgency of this research was to provide references for educators in choosing gamification platforms that are effective for improving learning outcomes and efficient for use as assessment media. This research was comparative quantitative research with a true experimental design. The data analysis technique used was one-way ANOVA with a sample of 57 students. The results stated that there were differences in student learning outcomes that were gamified via Kahoot, Quizizz, and Wordwall. This hypothesis was taken because the analysis results in the ANOVA table show a significance value of 0.013 <0.05, meaning that there are differences in student learning outcomes, so the H1 hypothesis was accepted and the H0 hypothesis was rejected. Furthermore, the results of the post hoc test analysis state that Quizizz was more effective in improving student learning outcomes compared to groups that are gamified via Kahoot and Wordwall. This was evidenced by the average learning outcomes in the Quizizz group of 9.00, which were the highest compared to the Kahoot and Wordwall groups.